Immunocytochemical analysis of human synovial lining cells: phenotypic relation to other marrow derived cells. Issue 5 (May 1991) - Athanasou, N A; Quinn, J
Abstract : The antigenic phenotype of human synovial lining cells in normal and hyperplastic synovium intima was determined with a panel of monoclonal antibodies directed against a large number of well defined myeloid (macrophage/granulocyte associated) antigens. Synovial lining cells express numerous macrophage associated antigens, including CD11b (CR3), CD13, CD14, CD16 (FcRIII), CD18, CD32 (FcRII), CD45 (leucocyte common antigen), CD54 (ICAM-1), CD64 (FcRI), CD68, and CD71 (transferrin receptor). Few synovial lining cells expressed CD11a (LFA-1) and CD11c (p150, 95). Subintimal macrophages expressed all the macrophage associated antigens which were present on synovial lining cells and, in addition, expressed CD15a, CD25 (interleukin-2 receptor), CD34, and CD35 (C3b receptor), none of which was present on synovial lining cells. Synovial lining cell expression of a wide range of macrophage antigens argues in favour of their marrow origin and membership of the mononuclear phagocyte system.